IMPLICATIONS IN DESIGNING READING MATERIALS FOR EFL LEARNERS - Oralbaeva Ayzada; Qodirova Maftuna Davronovna (TADQIQOTLAR.UZ, 2024)
This research aims at developing the Intensive Reading material for the second- semester students of English Language Education Program. It is a Research and Development study that was done by using Reeves’ (2000) Design-Based Research model. The analysis showed that the intensive reading skills are still considered difficult for some students. Additionally, the content of the product is based on the syllabus and the Outcome Based Education (OBE) curriculum. The researcher developed 11 units of Intensive Reading material based on the previous needs analysis data. It covers materials related to the intensive reading skills such as scanning, skimming, previewing, predicting, building a powerful vocabulary, context clues, and understanding topic, main idea, and paragraph are also included in the final product.